Large deviations for tandem queueing systems. (1994) - Dobrushin, Roland L.; Pechersky, Eugene A.
Abstract : The crude asymptotics of the large delay probability in a tandem queueing system is considered. The main result states that one of the two channels in the tandem system defines the crude asymptotics. The constant that determines the crude asymptotics is given. The results obtained are based on the large deviation principle for random processes with independent increments on an infinite interval recently established by the authors.